2010
DOI: 10.5660/kjws.2010.30.1.034
|View full text |Cite
|
Sign up to set email alerts
|

Allelopathic Effects of Common Ragweed (Ambrosia artemisifolia var. elatior) on the Germination and Seedling Growth of Crops and Weeds

Abstract: Competitive ability, allelopathy, made the common ragweed (Ambrosia artemisiifolia var. elatior) one of the most dangerous weeds in Korea. The aim of this research was to evaluate the role of common ragweed as test species under laboratory bioassay and glasshouse conditions. Inhibition effect of the leaf extract was higher than that of stem and root parts extracts on germination and seedling growth of weeds. The 5% concentration of leaf extract of common ragweed inhibited the germination rate of Echinochloa cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 16 publications
0
7
0
1
Order By: Relevance
“…Pisula and Meiners (2010a) and Csiszár et al (2012) reported the same effect in the treatment with water extract of giant goldenrod, but they also used only leaves for preparation of water extracts. Choi et al (2010) determined the inhibition of germination for 68.3%, 74.6% and 87.3% on different test-species in treatments with leaf extract of ragweed. Šćepanović et al (2007) confirmed the inhibitory effect of velvetleaf and jimsonweed extracts on germination of maize.…”
Section: Discussionmentioning
confidence: 99%
“…Pisula and Meiners (2010a) and Csiszár et al (2012) reported the same effect in the treatment with water extract of giant goldenrod, but they also used only leaves for preparation of water extracts. Choi et al (2010) determined the inhibition of germination for 68.3%, 74.6% and 87.3% on different test-species in treatments with leaf extract of ragweed. Šćepanović et al (2007) confirmed the inhibitory effect of velvetleaf and jimsonweed extracts on germination of maize.…”
Section: Discussionmentioning
confidence: 99%
“…2008). As a result of its early emergence, rapid growth during the juvenile phase, and possible allelopathic effect on neighboring species (Choi et al . 2010; Lehoczky et al .…”
mentioning
confidence: 99%
“…Zahvaljujući visokoj stopi klijavosti, brzom početnom porastu, visokoj stopi fotosinteze (C3 put) i alelopatskom delovanju na druge vrste u okruženju (Choi et al, 2010;Lehoczky et al, 2010), ambrozija se svrstava u visoko kompetitivne vrste sa velikim potencijalom za širenje (Brandes and Nitzsche, 2006). Njena konkurentska sposobnost zasnovana je na morfološkim osobinama, a pre svega visini, zatim masi pojedinih biljnih delova i rasporedu listova, odnosno distribuciji lisne površine i zavisi od stepena razvijenosti njenih pojedinih organa.…”
Section: Kompetitivnostunclassified